2007
DOI: 10.4161/cam.1.3.5114
|View full text |Cite
|
Sign up to set email alerts
|

Cell to Cell Signalling via Exosomes Through esRNA

Abstract: Exosomes are small vesicles of endosomal origin that can be released by many different cells to the microenvironment. Exosomes have been shown to participate in the immune system, by mediating antigen presentation. We have recently shown the presence of both mRNA and microRNA in exosomes, specifically in exosomes derived from mast cells. This RNA can be transferred between one mast cell to another, most likely through fusion of the exosome to the recipient cell membrane. The delivered RNA is functional, as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
198
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(203 citation statements)
references
References 18 publications
3
198
0
2
Order By: Relevance
“…Exosomes contain classical membrane marker proteins such as tetraspanins, adhesion proteins, and metalloproteinases that distinguish them from other vesicular structures such as apoptotic vesicles (23). Exosomes are considered to play an important role in intercellular communication either by target cell uptake or by inducing cell signaling via membrane receptors (24,25). In addition to membrane proteins, exosomes also carry mRNA, as well as ncRNA (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes contain classical membrane marker proteins such as tetraspanins, adhesion proteins, and metalloproteinases that distinguish them from other vesicular structures such as apoptotic vesicles (23). Exosomes are considered to play an important role in intercellular communication either by target cell uptake or by inducing cell signaling via membrane receptors (24,25). In addition to membrane proteins, exosomes also carry mRNA, as well as ncRNA (i.e.…”
mentioning
confidence: 99%
“…In addition to membrane proteins, exosomes also carry mRNA, as well as ncRNA (i.e. miRNA), and are thought to affect gene regulation in the target cells (24,26). Viruses such as Epstein-Barr virus and Kaposi sarcoma-associated herpesvirus encode miRNAs that are exported out of the infected cell via exosomes (27)(28)(29)(30), and exosomally transported miRNAs are functional in recipient cells and alter their cellular fate (27,30,31).…”
mentioning
confidence: 99%
“…Moreover, TLR7 recognizes microRNAs (miRNAs), particularly let-7 [20] , miR-21, and miR-29a [21] . Because microRNAs are present in exosomes [22,23] , it has been suggested that cells release miRNA into the environment via exosomes, activating TLR7 in other cells [20,21] . Interestingly, in this model, the effect of miRNA on other cells is not via the canonical pathway, in which miRNAs complementarily bind to mRNA and reduce the expression of the targeted mRNA.…”
Section: Endosomal Tlrs and Their Ligandsmentioning
confidence: 99%
“…Types of tumor cells such as ovarian cancer, chronic myelogenous leukemia were demonstrated to secret functional exosomes (Cho et al, 2011;Clayton et al, 2011;Hood et al, 2011;Taverna et al, 2012). Studies have reported that the exosomes implicated in the cell-to-cell signaling (Lotvall et al, 2007), involve in presentation of Ags to T cells in the immune system (Prado et al, 2008) and the exosomes from tumor cells promote the immune response to tumors by presentation of tumor Ags (Rountree et al, 2011). However, it has also been reported that exosomes from murine mammary tumor cells including TS/A and 4T1 cells can inhibit NK cells cytolytic activity by down-regulation of the expression of perforin, exosomes from breast tumors inhibit the activation of T cells (Liu et al, 2006).…”
Section: Exosomes From Murine-derived Gl26 Cells Promote Glioblastomamentioning
confidence: 99%